PENERAPAN SUPERVISI MANAJERIAL UNTUK MENINGKATKAN KINERJA KEPALA SEKOLAH DALAM BIDANG PENGELOLAAN PEMBELAJARAN DAN KESISWAAN - Siti Helia Fitriana; Wasidi (DIADIK, 2022)
This study aims to describe the application of managerial supervision to improve the performance of madrasah principals in the field of learning and student management at MTs Kota Pagaralam. The research method used is School Action Research conducted by madrasad supervisors. The subjects of this study were the Head of MTs Negeri 1 Pagaralam, Head of MTs GUPPI, Head of MTs YPI and Head of MTs Al-Azhar. The technique of collecting data is through observation, interviews, and documentation studies, while the analysis and interpretation of data uses a tracking process and systematic arrangement of interview transcripts, field notes, and other materials collected and to check the veracity of the data the researchers use triangulation by comparing them to data from another source. The results showed that the application of managerial supervision to improve the performance of school principals in the field of learning and student management at MTs Negeri 1 Pagaralam got a very good category. good, namely the Head of GUPPI Pagaralam was able to show evidence of complete and quite convincing performance, MTs YPI Pagaralam got a good category, namely the Head of YPI Pagaralam was able to show evidence of complete and quite convincing performance, and MTs Al-Azhar Pagaralam got a good category, namely Head Al-Azhar Pagaralam was able to show evidence of complete and quite convincing performance. The better the ability of the madrasah principal in implementing managerial supervision and the cooperation between madrasah residents, the better the work of the madrasah principal.